The Influence of Destination Image on Tourist Intention and Decision to Visit Tourist Destination (A Case Study of Pemuteran Village in Buleleng, Bali, Indonesia) - Satyarini, Ni Wayan Marsha; Rahmanita, Myrza; Setarnawat, Sakchai (Jurnal Penelitian Pariwisata, 2017)
This study examines the effects of the destination image to tourist intention and decision to visit tourism destination in Pemuteran Village, Bali. Destination image is an independent variable, tourist intention to visit serves as an intervening variable and decision to visit is a dependent variable. Explanatory research with quantitative method is employed. The number of sample is 112 respondents. Purposive sampling techniques is applied with criteria of Pemuteran village tourists. Data are collected with questionnaires and processed with path analysis. These results indicate that the variable destination image has a direct and significant effect on tourist intention to visit by 11.3%. Variable destination image has a direct and significant influence on the decision to visit by 37.5%. Variable tourist intention to visit has been direct and significant influence on the decision to visit amounted to 16.2%. Based on these results, Pemuteran village should keep trying to build a positive image and to improve the communication between the local government and local communities to strengthen cooperation to improve the natural environment in Pemuteran village.